Traumatic Thoracic and Lumbar Spine Injury in Adult Population Presenting to a Tertiary Care Hospital - Parajuli, Bikash; Kayastha, Sabik; Thapa, Jagadish; Shrestha, Dipak (Journal of Nepal Health Research Council, 2022)
Background: Epidemiology of traumatic thoracolumbar spine injury is a less explored subject in developing/ underdeveloped countries. The number of available studies in Nepal is even smaller. This study aims to establish the epidemiological characteristics of patients with thoracic and lumbar spine injuries presenting to Dhulikhel Hospital, Kathmandu University Hospital in Nepal.Methods: This is a single-center retrospective observational study. Patients with traumatic thoracolumbar spine injuries admitted to to Dhulikhel Hospital, Kathmandu University Hospital from 2015 January to 2019 December were included. International Spinal Cord Injury core data set (version 2) and International Spinal Cord Injury Spinal Column Injury Basic Data Set (version 1.0) were used for data collection. Results: Three hundred and seventeen patients were included, of which, 50.2% were male and the mean age was 45.5 ± 17 years. Fall was the most common etiology of injury (69.1%). The most common level of injury was L1 (32.5%). Thirty-seven patients (11.7%) had ASIA A neurology. One hundred and seventy-three (54.6%) patients underwent surgical intervention. The median hospital stay of the patients was 7 days (IQR: 3-11) with no recorded in-hospital mortality.Conclusions: Males and females are equally vulnerable to thoracic and lumbar spinal injuries, with the majority of patients in 46-60 age groups. More than 1/3rd neurologically impaired patients are with ASIA A neurology. The findings of this study can contribute to traumatic thoracic and lumbar spine injury prevention and rehabilitation.Keywords: Epidemiology; injury; lumbar spine; thoracic spine